2010
DOI: 10.1152/ajpgi.00322.2010
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor Nrf2 regulates SHP and lipogenic gene expression in hepatic lipid metabolism

Abstract: Nuclear factor erythroid-2 related factor 2 (Nrf2) plays a pivotal role in cytoprotection against both endogenous and exogenous stresses. Here, we establish a novel molecular link between Nrf2, nuclear receptor small heterodimer partner (SHP; NROB2), lipogenic genes, and hepatic lipid homeostasis. Deletion of Nrf2 (Nrf2⁻(/)⁻) in mice resulted in a reduced liver weight, a decrease in fatty acid content of hepatic triacylglycerol, as well as concomitant increases in the levels of serum VLDL-triglyceride (TG), HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
148
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(160 citation statements)
references
References 42 publications
12
148
0
Order By: Relevance
“…These mice show reduced liver weight, hepatic fatty acid content as well as serum lipids [60] . Furthermore, in hepatocytes of the Nrf2-/-mice, the expression level of PPARγ gamma, fatty-acid synthase, stearoylCoA desaturase and regulatory-element binding protein that are involved in de novo lipogenesis were found to be reduced [60] . We suggest that the role of the Nrf2 system in lipid homeostasis is certain but complex.…”
Section: Role Of the Nrf2 System In Regulating Insulin Signaling And mentioning
confidence: 97%
“…These mice show reduced liver weight, hepatic fatty acid content as well as serum lipids [60] . Furthermore, in hepatocytes of the Nrf2-/-mice, the expression level of PPARγ gamma, fatty-acid synthase, stearoylCoA desaturase and regulatory-element binding protein that are involved in de novo lipogenesis were found to be reduced [60] . We suggest that the role of the Nrf2 system in lipid homeostasis is certain but complex.…”
Section: Role Of the Nrf2 System In Regulating Insulin Signaling And mentioning
confidence: 97%
“…GABP deficiency may protect against diet-induced weight gain, obesity, and glucose intolerance; GABP also impairs adipogenesis, as it decreases adipose tissue mass and adipocyte size (Zhang et al 2012) and modulates hepatic lipid homeostasis (Huang et al 2010). Therefore, GABP downregulation could have improved insulin sensitivity and directly decreased fatty acid content of hepatic triacylglycerols of the eWAT-transplanted Lep ob/ob mice.…”
Section: Novel Pathways Involved In Nafldmentioning
confidence: 99%
“…C/EBPβ promotes adipocyte differentiation, through the activation of C/EBPα and PPARγ. It has also been reported that exogenous PPARγ could affect the conversion of pre-adipocytes into mature fat cells (Huang et al, 2010;Yasmeen et al, 2012). Flavonoids are a type of plant polyphenols, with low molecular weight compositions.…”
Section: Introductionmentioning
confidence: 99%